Positive association of alcohol consumption with incidence of hypertension in adults aged 40 years and over: Use of repeated alcohol consumption measurements. Issue 10 (October 2020) - Jung, Sukyoung; Kim, Mi Kyung; Shin, Jinho; Lee, Nakyoung; Woo, Hye Won; Choi, Bo Youl; Shin, Min-Ho; Shin, Dong Hoon; Lee, Young-Hoon
Summary: Background & aims: Managing alcohol consumption may be an effective way of preventing hypertension, which is an important modifiable risk factor for cardiovascular diseases. However, there is little evidence on the temporal relationship between alcohol consumption and incidence of hypertension. We investigated the prospective association between repeated measures of alcohol consumption and hypertension incidence among Korean adults aged 40 and over. Methods: This study included a total of 4989 participants that were not taking antihypertensive drugs and had normal blood pressure (BP) (systolic < 140 mmHg and diastolic < 90 mmHg). We used three measures of alcohol consumption (baseline, most recent, and average) as exposures and compared the three approaches. Using a modified Poisson regression model with a robust error estimator, we estimated incidence rate ratios (IRRs) and 95% confidence intervals (CIs) for hypertension. Results: Over a total of 17, 689 person-years (average 3.5 years of follow-up), 574 incident cases of hypertension were identified. In multivariable models, consuming ≥30 ml/d of alcohol was associated with a risk of hypertension among men (IRR = 1.72, 95% CI = 1.20–2.48, p trend = 0.017 for baseline alcohol consumption; IRR = 1.69, 95% CI = 1.23–2.33, p trend = 0.005 for the most recent alcohol consumption; IRR = 1.49, 95% CI = 1.09–2.03, p trend = 0.014 for average alcohol consumption). After additional adjustment for baseline BP the positive association remained only when the most recent alcohol consumption measure was used. There was no significant association between alcohol consumption and hypertension among women, and no interaction effect between alcohol consumption and baseline BP levels on incidence of hypertension (all p interaction > 0.05) existed. Conclusions: Alcohol consumption, especially consuming ≥30 ml/d, may be positively linked with incidence risk of hypertension among men.